Effect of gradient field nonlinearity distortions in MRI-based attenuation maps for PET reconstruction. (March 2017) - Lundman, Josef A; Johansson, Adam; Olofsson, Jörgen; Axelsson, Jan; Larsson, Anne; Nyholm, Tufve
Highlights: The effect of gradient field non-linearity distortions on PET AC was investigated. <±5% SUV quantification error for ±2.3 mm geometrical distortion at 15 cm radius. An upper limit of 2 mm residual distortion at 15 cm is proposed for PET/MRI AC. Abstract: Purpose: Attenuation correction is a requirement for quantification of the activity distribution in PET. The need to base attenuation correction on MRI instead of CT has arisen with the introduction of integrated PET/MRI systems. The aim was to describe the effect of residual gradient field nonlinearity distortions on PET attenuation correction. Methods: MRI distortions caused by gradient field nonlinearity were simulated in CT images used for attenuation correction in PET reconstructions. The simulations yielded radial distortion of up to ± 2.3 mm at 15 cm from the scanner isocentre for distortion corrected images. The mean radial distortion of uncorrected images were 6.3 mm at the same distance. Reconstructions of PET data were performed using the distortion corrected images as well as the images where no correction had been applied. Results: The mean relative difference in reconstructed PET uptake intensity due to incomplete distortion correction was less than ± 5 % . The magnitude of this difference varied between patients and the size of the distortions remaining after distortion correction. Conclusions: Radial distortions of 2 mm at 15 cm radius from the scanner isocentre lead to PET attenuation correction errors smaller than 5%. Keeping the gradient field nonlinearity distortions below this limit can be a reasonable goal for MRI systems used for attenuation correction in PET for quantification purposes. A higher geometrical accuracy may, however, be warranted for quantification of peripheral lesions. These distortions can, e.g., be controlled at acceptance testing and subsequent quality assurance intervals.